AUDITORÍA DE GESTIÓN AL DEPARTAMENTO DE CRÉDITO DE LA COOPERATIVA DE AHORRO Y CRÉDITO CRISTO REY, PERÍODO 2017 - Sucunuta Medina, Graciela Magdalena (2020)
The thesis called “MANAGEMENT AUDIT TO THE CREDIT DEPARTMENT OF THE SAVINGS AND CREDIT COOPERATIVE CRISTO REY, PERIOD 2017” was developed with the purpose of serving as a mechanism of economic, financial and administrative assistance to determine compliance and execution by staff of the credit department, for this purpose, objectives were set to evaluate the efficiency, effectiveness and economy of the material, financial, human and technological resources that were used, and also comply with the prerequisite to choose the Degree and Title of Accounting and Audit Engineer. For the fulfillment of the objectives, various methods were developed according to the audit process, based on the preliminary knowledge with the visit to the Cristo Rey Credit Saving Cooperative where the information necessary for the development of the audit was collected, the efficiency was evaluated , efficiency and economy, questionnaires were designed and applied for each component (Administrative, Account Opening and Credits, Credit Granting) activities carried out by the Credit Department, this management instrument allowed to quantify the level of confidence and therefore determine the level of risk in the activities carried out by the Credit Department. Management indicators were applied to measure the efficiency, effectiveness, economy and quality of the services provided by the credit 5 department, where the respective comments and suggestions were issued to achieve the achievement of institutional goals and objectives. In order to verify compliance with the legal provisions, the internal control system was evaluated by preparing the respective narrative certificates, and in turn the pertinent recommendations were issued to improve each failure, various analyzes were carried out through analytical certificates to corroborate the compliance of the processes , fundraising, credit granting, and recovery. It was found that in the internal control system of the Cooperative there are some shortcomings not considered serious but important to take into account and implement improvements for the process in relation to portfolio recovery and credit granting. Finally, the management audit report was prepared and presented, which contains a series of comments, conclusions and recommendations, which will help the entity to meet its institutional objectives and goals efficiently and effectively; the same that was socialized and put to the consideration of the highest authority of the Cooperative.